(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate painful symptoms after endodontic treatment, in a single session, on uniradicular teeth with pulp necrosis, varying two techniques of foramen patency: with and without previous preparation of the cervical and middle thirds. Patients were randomly divided into two groups (n = 23). SSP Group (Without Previous Preparation): the endodontic treatment was performed with Wave One Gold files (Dentsply Sirona, Ballaigues - Switzerland) associated with the patency with ProGlider (Dentsply Sirona, Ballaigues - Switzerland) prior to the preparation of the cervical and middle thirds. CPP Group (with Previous Preparation): endodontic treatment was performed with Wave One Gold files associated with patency with ProGlider after the preparation of the cervical and middle thirds. Irrigation was carried out with 2.5% NaOCl and the channels were filled using the single cone technique with AH Plus cement, using the McSpadden compactor. After treatment, the patients answered a questionnaire with the VAS pain scale, and rated it from 0 to 10, in the periods of 24 hours, 72 hours, and 1 week after treatment. The data were analyzed using the Mann-Whitney, Kruskal-Wallis (Student-Newman-Keuls) Dunn test and Chi-square test. The results showed that in patients who had previously prepared the cervical and middle thirds, there were no statistical differences between pain scores at different experimental times (p = 0.328). The comparison of pain after 24 hours and 72 hours showed statistically similar values (p = 0.384), as did the comparison of 72 hours with one week (p = 1.00). The group without prior preparation revealed significant differences between the results (p = 0.046). Dunn’s complementary test showed that the differences were limited to pain scores after 24 hours and the results after one week (p = 0.042). The Mann-Whitney test, applied to data obtained in both experimental groups, revealed that at 24 hours (p = 0.562), 72 hours (p = 1.00) and 1 week (p = 1.00), there were no differences between the types of preparation performed. It was concluded that the levels of pain after endodontic treatment in uniradicular teeth with pulp necrosis with or without previous preparation of the cervical and middle third of the canal presented an equivalent behavior.